Pengaruh Pemberian Variasi Dosis Rifampisin Terhadap Kadar Gamma Glutamyl Transferase dan Alkaline Phosphatase Pada Tikus Putih Galur Wistar - Jeharu, Sofiana Agustin; Putra, I Gusti Putu Agus Ferry Sutrisna; Widayanti, Ni Putu (Bali International Scientific Forum, 2020)
Background: Tuberculosis is a contagious infectious disease caused by the bacterium Mycobacterium tuberculosis. Rifampicin is a first-line drug for the treatment of tuberculosis. Rifampicin has a bactericidal effect and the sterilizing effect is effective against intracellular and extracellular tuberculosis bacteria. In addition, one of the side effects of using rifampicin is hepatotoxicity. Objective: to determine the effect of rifampicin drug dosage on GGT and ALP levels in wistar rats. Methods: using an experimental study design with the pretest and posttest control group design method with the use of test animals 24 wistar rats divided into 4 groups. The technique of analyzing data using SPSS One Way Annova was followed by a Post-Hoc Test. Results: The results of the study showed an average increase in GGT levels in treatment groups 1, 2 and 3 was 29.5%, 40.9% and 55.4% and the mean increase in ALP levels in treatment groups 1, 2 and 3 was 27.5 %, 46.7% and 53.5%. The One Way ANOVA test results obtained p = 0.00 (p <0.05) followed by the Post Hoc test obtained α> 0.05. Conclusions: there was a significant effect on the levels of GGT and ALP after the administration of dose variations of the rifampicin drug in wistar strain white rats.